YIIFSWA II OPENDAY - Interview with Perpetua Iyere-Usiahon - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Perpetua Iyere-Usiahon, FMARD, Nigeria. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam